Sonographic Findings of Common Musculoskeletal Diseases in Patients with Diabetes Mellitus - Park, Minho; Park, Ji Seon; Ahn, Sung Eun; Ryu, Kyung Nam; Park, So Young; Jin, Wook (Korean journal of radiology, 2016)
Diabetes mellitus (DM) can accompany many musculoskeletal (MSK) diseases. It is difficult to distinguish the DM-related MSK diseases based on clinical symptoms alone. Sonography is frequently used as a first imaging study for these MSK symptoms and is helpful to differentiate the various DM-related MSK diseases. This pictorial essay focuses on sonographic findings of various MSK diseases that can occur in diabetic patients.